Effect of affordability of alcohol on the level of alcohol consumption in Russia - Razvodovsky YE (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Objective: To study the relationship between the affordability of alcohol and the level of its sale, the total level of consumption, as well as the consumption of unrecorded alcohol in Russia in the post-Soviet period.  Methods: A comparative analysis of the dynamics of the affordability of alcohol, the level of its sale, the total level of consumption, as well as the consumption of unrecorded alcohol in Russia in the period from 1991 to 2015 was carried out. Statistical analysis (Spearman's correlation, linear regression) was carried out using the STATISTICA 10 package.  Results: The affordability of alcohol is positively correlated with the sale of alcohol (r=0,64; p<0.000) and negatively correlated with the total level of alcohol consumption (r=-0,4; p<0.000), as well as the level of unrecorded alcohol consumption (r=-0,77; p<0,000).  Conclusions: This study revealed the positive relationship between affordability of alcohol and the level of alcohol sales, as well as negative relationship between affordability of alcohol and unregistered alcohol consumption in Russia.